2006
DOI: 10.1021/cm061344c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of New Polyaniline/Nanotube Composites Using Ultrasonically Initiated Emulsion Polymerization

Abstract: Ultrasonically initiated, in situ emulsion polymerization was used to prepare multiwalled carbon nanotube/polyaniline composites (MWNTs/PANI). Transmission electron microscopy (TEM) showed that the nanotubes were coated with a PANI layer, with the thickness of this coating varying with the content of carbon nanotubes and polymerization conditions. Whereas polyaniline/carbon nanotube composite particles prepared by the conventional stirring method have a highly structured, nodular morphology, ultrasonic initiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
113
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(120 citation statements)
references
References 36 publications
6
113
0
Order By: Relevance
“…The acid-treatment did not change the crystalline order of CNT. For PANI, the characteristic peaks appeared at 15.3°, 20.4°and 25.4°, corresponding to (0 1 1), (0 2 0) and (2 0 0) crystal planes of PANI [33,34]. The data indicates that no additional crystalline order has been introduced into the composite.…”
Section: Characterization and Measurementsmentioning
confidence: 93%
“…The acid-treatment did not change the crystalline order of CNT. For PANI, the characteristic peaks appeared at 15.3°, 20.4°and 25.4°, corresponding to (0 1 1), (0 2 0) and (2 0 0) crystal planes of PANI [33,34]. The data indicates that no additional crystalline order has been introduced into the composite.…”
Section: Characterization and Measurementsmentioning
confidence: 93%
“…Zhang et al have demonstrated that the polymeric acid has significant effect on the morphology and size of the polyaniline nanotubes [5]. Many techniques have been used to synthesize PANI nanostructure such as stirring [6][7][8], static placement, [9] sonication [10][11][12], and emulsion polymerization [13][14][15][16]. Particularly, conducting polymer nanotubes and nanofibers have received growing interest in recent years due to their unique properties and promising potential applications in nanodevices [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…The shape and intensity of the C 1s, N 1s and O 1s spectra changed with increase in the treatment time, results that corresponded to the ratio of each atom in the wide spectra. The intensity of sp 2 peak at the [28,29]. The XPS C 1s and N 1s spectra indicated that oxide and nitride functional groups such as -CO, -NO and -NH 2 were fabricated on the MWNT surfaces by N 2 atmospheric pressure plasma treatment.…”
Section: Resultsmentioning
confidence: 98%